The Role of MRI Pancreatic Protocol in Assessing Response to Neoadjuvant Therapy for Patients With Borderline Resectable Pancreatic Cancer - Hussien, Nervana; Hussien, Rasha S.; Saad, Darine Helmy Amin; El Kassas, Mohamed; Elkhatib, Walid F.; Ezz El Din, Mai (Frontiers in Oncology, 2022)
Abstract Background: Borderline Resectable Pancreatic Cancer (BRPC) remains a unique entity that is difficult to categorize due to variance in definitions and the small number of patients. The ultimate goal is to achieve a free resection (R0) after a favorable response to neoadjuvant therapy that is somewhat difficult to assess by current radiological parameters. Aim: To evaluate the role of Magnetic Resonance Imaging (MRI) pancreatic protocol, including Diffusion-Weighted Imaging (DWI) in patients with BRPC receiving neoadjuvant therapy, and further compare it to RECIST criteria and outcome. Methods: Histologically confirmed BRPC patients were prospectively included. DWI MRI was performed pre and post-therapy. Clinical characteristics with ensuing operability were recorded and correlated to radiological RECIST/ apparent diffusion coefficient (ADC) change, Preoperative therapy administrated, surgical resection status, and survival. Results: Out of thirty BRPC cases, only 11 (36.7%) ultimately underwent pancreaticoduodenectomy. Attaining a stationary or stable disease via ADC/RECIST was achieved in the majority of cases (60%/53.3% respectively). Of the 12 patients (40 %) who achieved a regression by ADC, 11 underwent surgery with an R0 status. These surgical cases showed variable RECIST responses (PR=5, SD=4, PD=3). Responders by ADC to neoadjuvant therapy were significantly associated to presenting with abdominal pain ( p =0.07 ), a decline in post-therapy CA 19-9 (p<0.001), going through surgery (p<0.001), and even achieving better survival (p<0.001vs. 0.66 ). Conclusion: DWI-MRI ADC picked up patients most likely to undergo a successful operative procedure better than traditional RECIST criteria. An algorithm incorporating novel radiological advances with CA19-9 deserves further assessment in future studies